Effects of weak rock geomechanical properties on tunnel stability - Ghiasi, Vahed (2012)
Numerous tunnels are constructed in various parts of the world. Various technologies such as the Tunneling Boring Machine (TBM), New Austrian Tunneling Method (NATM), cut and cover method, and drilling and blasting method are used in order to aid tunnel constructions. In order to investigate the behavior of tunnels and to enhance these technologies, it is primarily important to investigate the issues pertaining to the soil and rock structure interaction. It is also of prime importance to study their impact on the tunnel system‟s performance. In engineering practice, geotechnical problems such as settlement and ground stability are not given due consideration in tunnel crossing constructions on the ground surface in urban areas. In order to deal with the challenges of geotechnology, full scale experiments may be performed. However it may not be feasible to conduct full scale experiments as it may be expensive. The main purpose of this thesis is to evaluate the ground behavior in terms of deformation and strength parameters related to tunnel stability in different geomaterials such as weak rocks. This thesis has contributed vastly towards the understanding of the effects of tunnel structures on the geomaterials surrounding the tunnel and interaction between them. The main methods employed in this thesis are based on desk studies (theoretical investigation), laboratory tests, field investigations and the use of computer softwares. Advanced constitutive models were used in geometrical applications for numerical simulation of linear and non-linear, time-dependent and anisotropic behavior of soil and weak rocks. Unique procedures are required in order to deal with hydrostatic and non-hydrostatic pore pressures. These are needed as soil and rock are multi-phase materials. Although the modeling of the soil and rock itself is an important issue, many tunnel projects involve the modeling of structures and the interaction between the structures and the soil and rock. Numerical simulations with the Finite Element Method (FEM) and Finite Deferential Method (FDM) were conducted to analyze in order to evaluate the influence of stress on displacement and other factors in the process. It is of prime importance to identify the mechanical properties of rock and soil. This is significant to assess the stability of tunnels as the design of support system is one of the most important steps in tunneling. Lack of knowledge of geo-mechanical and physical properties such as the mechanical behavior of the materials surrounding the underground or surface structure would make it impossible to offer suitable supervision, propose methods for an appropriate design, or predict risks with a reasonable degree of accuracy. The current thesis contributes in various ways to enhance existing knowledge. Some of the significant areas are (i) the plan which has been developed for the design of tunnels; the plan for tunnel design and studding in rocks which contains the theoretical, and experimental investigations, including charts and graphs, of Karaj and North Water Convey Tunnel (NWCT) path and its stability analysis in Iran and electrified double track tunnel project between Ipoh and Padang Besar which is the longest rail tunnel project in Malaysia (ii) Evaluation of the squeezing potential of tunnels is presented in this thesis with significant results, (iii) Proposed method for evaluation of squeezing potential in rock tunnel which is Tunnel Instability Ranking(TIR), (iv) using numerical methods (FEM and FDM) to analyze the management of stability and hazards in tunnel construction. Another contribution is the studies regarding the modulus of elasticity and compressive strength in weathered granite, which is related to tunnel stability. The results derived from the analysis indicate that tunnels in faulted regions are unstable and it is crucial to provide strong supports in these regions. The studies on the strength parameters and grain size of weathered granites revealed trends that show strength increases with decreasing grain size. It has been noted that with increased weathering, the modulus of elasticity decreases linearly with a decreasing uniaxial compressive strength.